2020
DOI: 10.3390/nu12030751
|View full text |Cite
|
Sign up to set email alerts
|

Dietary-Lifestyle Patterns Associated with Adiposity and Metabolic Abnormalities in Adult Men under 40 Years Old: A Cross-Sectional Study (MeDiSH Project)

Abstract: The aim of this study was to examine the associations of dietary-lifestyle patterns (DLPs) with adiposity and metabolic abnormalities in adult Polish men that were under 40. The cross-sectional study included 358 men that were 19–40-year-old. Dietary and lifestyle data were collected with multicomponent food frequency questionnaire (KomPAN®). DPLs were derived with Principal Component Analysis (PCA) using 25 dietary and six lifestyle as the input variables. Adiposity was determined with the use of: overweight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 32 publications
1
16
0
Order By: Relevance
“…Interestingly, no significant association between self-reported eating behaviour and age or SES was found in the present study. This research was conducted among university students, and the participants’ SES characteristics were, to some extent, similar to other studies conducted among adolescents and young adults in Poland [ 7 , 33 , 40 ]. Some other studies demonstrated significant associations between some of the eating behaviour dimensions and age or SES.…”
Section: Discussionmentioning
confidence: 74%
“…Interestingly, no significant association between self-reported eating behaviour and age or SES was found in the present study. This research was conducted among university students, and the participants’ SES characteristics were, to some extent, similar to other studies conducted among adolescents and young adults in Poland [ 7 , 33 , 40 ]. Some other studies demonstrated significant associations between some of the eating behaviour dimensions and age or SES.…”
Section: Discussionmentioning
confidence: 74%
“…To our knowledge, this is the first study to examine associations between a range of dietary and lifestyle behaviors as well as nutrition knowledge among Polish pharmacists. We used a validated, culture-specific, tool with reliable psychometric properties [9][10][11][13][14][15][16]. Our results revealed that dietary patterns among this group of health-care professionals are moderate and comparable to the general adult Polish population [11], with slightly higher values of both, the Pro-Healthy Diet Index (pHDI-10) and the Table 5 The mean values and interquartile ranges (Q25-Q75) of consumption frequencies of the selected food items together with the Pro-Healthy Diet Index (pHDI-10), the Non-Healthy-Diet-Index (nHDI-14) and nutrition knowledge test scores in our sample in comparison with Polish healthy population data [7].…”
Section: Discussionmentioning
confidence: 99%
“…A total of 358 men from the Warmia and Mazury region (Poland), aged 19–40 years old were analysed in this study ( Figure 1 ) [ 30 , 31 ]. Details of the sample recruitment have been previously reported [ 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…A total of 358 men from the Warmia and Mazury region (Poland), aged 19–40 years old were analysed in this study ( Figure 1 ) [ 30 , 31 ]. Details of the sample recruitment have been previously reported [ 31 ]. In brief, the study was publicly advertised using posters, social media advertising, and through direct contact with local businesses and council, inviting male employees to participate in the study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation